2022
DOI: 10.3390/nu14102037
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nutrition Knowledge and Skills by the Innovative Education Program MaestraNatura in Middle School Students of Italy

Abstract: Promoting a healthy diet, mainly in youths, is the most effective action to prevent and fight dietary excesses and nutritional imbalance in the population. MaestraNatura (MN) is an innovative nutritional education program aimed at promoting a healthy lifestyle in first-level secondary school students. The study evaluated the effectiveness of the MN program in improving knowledge in students following the MN program (MN group) with respect to a control group (CO group) undergoing a “traditional” nutritional edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Our results showed that the primary school students who underwent the nutrition education program MNP had more knowledge about nutrition, as assessed by the knowledge questionnaire, than those attending traditional programs, as was previously proven in middle school students [ 20 ].…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Our results showed that the primary school students who underwent the nutrition education program MNP had more knowledge about nutrition, as assessed by the knowledge questionnaire, than those attending traditional programs, as was previously proven in middle school students [ 20 ].…”
Section: Discussionsupporting
confidence: 70%
“…The improvement of knowledge is considered a necessary step to increase the population’s health literacy and, especially, food literacy, being proposed as effective tools in improving the adherence to adequate dietary habits [ 25 ], as also indicated in the “White Paper on nutrition-, overweight-, and obesity-related health issues”, published in 2008 by the European Commission [ 26 ]. However, increasing knowledge, although necessary, might not be enough to promote effective and long-lasting effects on dietary habits without a concomitant acquisition of skills that enable people to translate the theory in practice, i.e., to implement the food pyramid principles into their daily diets [ 20 , 27 , 28 ]. This aspect was highlighted in a recent systematic review that pointed out how nutrition education interventions based on practical activities are more likely to be successful in improving diet quality among children [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations